ANALYSIS OF TASK MANAGEMENT IN INCREASING EMPLOYEES PRODUCTIVITY DURING PANDEMIC AT PT. MANDALA FINANCE TILAMUTA BRANCH - suminto limbotu; Darman; sukriyanto (LP2M Universitas Bina Mandiri Gorontalo, 2022)
As for the purpose of this research is the analysis of task management in increasing employee productivity during the Pandemic Period at PT. Mandala Finance Tilamuta Branch.This research method uses three data collection techniques, namely observation, interviews, and documentation.The results of the study indicate that the management of tasks in the division of labor has not been able to give an effect on employee productivity. The workload has not been able to have an effect on employee work productivity. This is because the billing department has a workload such as billing customers who have different characters and conditions that are not possible, such as the current covid19 pandemic. Task management in work placements has not been able to have an effect on employee work productivity. Because this is due to the physical condition and age of employees, especially during a pandemic like this, of course, one must have a strong immune system in order to achieve employee work productivity